MODERASI PENDIDIKAN ISLAM STUDI KASUS BUMRUNG SUKSA ISLAMIC SCHOOL DI THAILAND SELATAN - Bashiroh, Saifiyatil; Khumaidi, Ahmad; Maghfiroh, Ummi Lailia (Universitas Tanjungpura, 2024)
Islamic education in Southeast Asia has its own dynamics and challenges, especially in countries with a majority non-Muslim population. One interesting case study is Bumrung Suksa Islamic School in Southern Thailand, an Islamic educational institution that has adapted to global dynamics and contemporary demands. This research uses a qualitative approach to explore the concept of moderation in Islamic education in this school. This approach involves in-depth interviews with teaching staff, students and school stakeholders, as well as analysis of documents related to the school